The Investment’s Impact on Economic Growth in Indonesia Considering Inflation, Interest Rates, and Exchange Rate Dynamics - Sastra Tamami; Tibrani Tibrani (Jurnal Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study examines how inflation, interest rates, and exchange rates affect Indonesia’s economic growth, highlighting investment as a mediating factor in this relationship. It addresses gaps in prior research by analyzing both direct and indirect effects of investment on growth outcomes. Methodology: A quantitative approach using SEM-PLS in SmartPLS 4.0 was applied to the questionnaire and macroeconomic data. The measurement and structural models were evaluated to test the relationships between macroeconomic variables and economic growth. Results: Inflation, interest rates, and exchange rates positively influence investments, significantly enhancing economic growth. Interest and exchange rates also have direct effects on growth, whereas inflation does not. Investment fully mediates the inflation–growth relationship and partially mediates the effects of interest and foreign exchange rates. Conclusions: Investment plays a critical role in linking macroeconomic conditions to economic growth, emphasizing its importance in policy strategies. Stable macroeconomic conditions contribute to investment growth, which, in turn, fosters economic expansion. Limitations: The study relies on cross-sectional and perception-based data, and future research should consider longitudinal and sectoral analyses to capture dynamic effects. Contributions: This study offers new insights into the mediating role of investment in Indonesia’s economic growth, providing both theoretical and policy implications that can guide future economic strategies.